Aspectos translacionais dos macrófagos no carcinoma de células escamosas da cavidade oral: uma revisão sistemática com meta-análise. - Costa e Silva, Luana Paula Borges da [UNESP] (Universidade Estadual Paulista (Unesp), 2026)
Oral squamous cell carcinoma (OSCC) is the most frequent malignant neoplasm of the oral cavity, characterized by heterogeneous biological behavior and a frequently unfavorable prognosis, despite therapeutic advances. The interaction between tumor cells and the tumor microenvironment has been widely investigated, particularly regarding the role of tumor-associated macrophages (TAMs). These macrophages can be identified by specific markers, such as CD68, which represents the total macrophage population, and CD163, associated with the M2 phenotype, characterized by immunosuppressive and pro-tumoral activity. The density and distribution of these macrophages within the tumor microenvironment may differ, demonstrating distinct correlations with neoplastic progression, invasiveness, and clinical prognosis. Objective: To evaluate, through a systematic review with meta-analysis, the differences in CD68⁺ and CD163⁺ macrophage density in patients affected by OSCC and to correlate this density with tumor characteristics. Methods: This systematic review was conducted in accordance with the guidelines of the Cochrane Handbook. The research protocol was registered on the Open Science Framework (OSF) online platform. Literature searches were performed in PubMed, Scopus, Cochrane Library, Embase, LILACS, SciELO, and Web of Science. The Rayyan software was used for duplicate removal, and the Joanna Briggs Institute (JBI) critical appraisal checklist for cross-sectional studies was applied to assess the risk of bias of the included articles. Results: A total of 1,659 articles were initially identified; after applying the inclusion and exclusion criteria, 24 were eligible for quantitative analysis. Following study assessment and eligibility evaluation, 8 articles were included in the present systematic review. Meta-analysis revealed higher expression of CD68⁺ and CD163⁺ markers in the tumor stroma compared with tumor nests, as well as a higher prevalence of CD68⁺ macrophages in tumors with moderately and poorly differentiated histological grades. CD163⁺ macrophages showed greater density in cases with lymph node metastasis. Regarding TNM staging and metastasis variables, the meta-analysis did not demonstrate significant differences in CD163⁺ expression among different stages or in the presence of distant metastasis. However, application of the GRADE scale indicated that these variables present low to very low levels of scientific evidence, respectively. Conclusion: It is concluded that higher densities of CD68⁺ and, particularly, CD163⁺ macrophages in the tumor microenvironment of oral squamous cell carcinoma are associated with less differentiated histological grades, lymph node metastasis, and the tumor stroma, suggesting their potential prognostic value. Keywords: Squamous

Oral squamous cell carcinoma (OSCC) is the most frequent malignant neoplasm of the oral cavity, characterized by heterogeneous biological behavior and a frequently unfavorable prognosis, despite therapeutic advances. The interaction between tumor cells and the tumor microenvironment has been widely investigated, particularly regarding the role of tumor-associated macrophages (TAMs). These macrophages can be identified by specific markers, such as CD68, which represents the total macrophage population, and CD163, associated with the M2 phenotype, characterized by immunosuppressive and pro-tumoral activity. The density and distribution of these macrophages within the tumor microenvironment may differ, demonstrating distinct correlations with neoplastic progression, invasiveness, and clinical prognosis. Objective: To evaluate, through a systematic review with meta-analysis, the differences in CD68⁺ and CD163⁺ macrophage density in patients affected by OSCC and to correlate this density with tumor characteristics. Methods: This systematic review was conducted in accordance with the guidelines of the Cochrane Handbook. The research protocol was registered on the Open Science Framework (OSF) online platform. Literature searches were performed in PubMed, Scopus, Cochrane Library, Embase, LILACS, SciELO, and Web of Science. The Rayyan software was used for duplicate removal, and the Joanna Briggs Institute (JBI) critical appraisal checklist for cross-sectional studies was applied to assess the risk of bias of the included articles. Results: A total of 1,659 articles were initially identified; after applying the inclusion and exclusion criteria, 24 were eligible for quantitative analysis. Following study assessment and eligibility evaluation, 8 articles were included in the present systematic review. Meta-analysis revealed higher expression of CD68⁺ and CD163⁺ markers in the tumor stroma compared with tumor nests, as well as a higher prevalence of CD68⁺ macrophages in tumors with moderately and poorly differentiated histological grades. CD163⁺ macrophages showed greater density in cases with lymph node metastasis. Regarding TNM staging and metastasis variables, the meta-analysis did not demonstrate significant differences in CD163⁺ expression among different stages or in the presence of distant metastasis. However, application of the GRADE scale indicated that these variables present low to very low levels of scientific evidence, respectively. Conclusion: It is concluded that higher densities of CD68⁺ and, particularly, CD163⁺ macrophages in the tumor microenvironment of oral squamous cell carcinoma are associated with less differentiated histological grades, lymph node metastasis, and the tumor stroma, suggesting their potential prognostic value. Keywords: Squamous
Translational aspects of macrophages in oral squamous cell carcinoma: a systematic review with meta-analysis.
Keywords: Carcinoma de células escamosas de cabeça e pescoço; Macrófagos; Antígeno CD163; Molécula CD68; Squamous cell carcinoma of head and neck; Macrophages; CD163 antigen; CD68 molecule